Assessment of Tumorigenic Potential in Mesenchymal-Stem/Stromal-Cell-Derived Small Extracellular Vesicles (MSC-sEV) - Thong Teck Tan; Ruenn Chai Lai; Jayanthi Padmanabhan; Wei Kian Sim; Andre Boon Hwa Choo; Sai Kiang Lim (MDPI AG, 2021)
Mesenchymal-stem/stromal-cell-derived small extracellular vesicles (MSC-sEV) have been shown to ameliorate many diseases in preclinical studies. However, translating MSC-sEV into clinical use requires the development of scalable manufacturing processes for highly reproducible preparations of safe and potent MSC-sEVs. A major source of variability in MSC-sEV preparations is EV producer cells. To circumvent variability in producer cells, clonal immortalized MSC lines as EV producer lines are increasingly being used for sEV production. The use of sEVs from immortalized producer cells inevitably raises safety concerns regarding the tumorigenicity or tumor promoting potential of the EV products. In this study, cells from E1-MYC line, a MSC cell line immortalized with the MYC gene, were injected subcutaneously into athymic nude mice. At 84 days post-injection, no tumor formation was observed at the injection site, lungs, or lymph nodes. E1-MYC cells pre-and post-sEV production did not exhibit anchorage-independent growth in soft agar. Daily intraperitoneal injections of 1 or 5 μg sEVs from E1-MYC into athymic nude mice with FaDu human head and neck cancer xenografts for 28 days did not promote or inhibit tumor growth relative to the xenograft treated with vehicle control. Therefore, MYC-immortalized MSCs are not tumorigenic and sEVs from these MSCs do not promote tumor growth.